Toward the Identification of a Specific Psychopathology of Substance Use Disorders - Maremmani, Angelo G. I.; Pani, Pier Paolo; Rovai, Luca; Bacciardi, Silvia; Maremmani, Icro (Frontiers in Psychiatry, 2017)
Addiction is a mental illness in which psychiatric conditions imply a prominent burden. Psychopathological symptoms in Substance Use Disorder patients are usually viewed as being assignable to the sphere of a personality trait or of comorbidity, leaving doubts about the presence of a specific psychopathology that could only be related to the toxicomanic process. Our research group at the University of Pisa has shed light on the possible definition of a specific psychopathological dimension in Substance Use Disorders. In Heroin Use Disorder patients, performing an exploratory principal component factor analysis (PCA) on all the 90 items included in the SCL-90 questionnaire led to a 5-factor solution. The first factor accounted for a depressive 'worthlessness and being trapped' dimension; the second factor picked out a ‘somatic symptoms’ dimension; the third identified a 'sensitivity-psychoticism' dimension; the fourth a 'panic-anxiety' dimension; and the fifth a 'violence-suicide' dimension. These same results were replicated by applying the PCA to another Italian sample of 1,195 heroin addicts entering a Therapeutic Community Treatment. Further analyses confirmed the clusters of symptoms, independently of demographic and clinical characteristics, active heroin use, lifetime psychiatric problems, kind of treatment received, and, especially, other substances used by the patient like alcohol or cocaine. Moreover, these clusters were able to discriminate patients affected by addiction from those affected by psychiatric diseases such as major depressive disorder. Our studies seem to suggest the trait- rather than the state-dependent nature of the introduced psychopathology dimensions of Substance Use Disorders.